Three-dimensional and volumetric thoracic growth in children with moderate idiopathic scoliosis compared with normal. Issue 3 (May 2017) - Charles, Yann Philippe; Marcoul, Amélie; Schaeffer, Mickaël; Canavese, Federico; Diméglio, Alain
Abstract : We aimed to measure thoracic dimensions and volume in relation to growth and verify the influence of scoliosis on thoracic growth. A reference group of 294 healthy volunteers was compared with a group of 557 patients with idiopathic scoliosis ranging in age from 3 to 25 years. The optical ORTEN system for trunk surface data acquisition was used to calculate thoracic volume, perimeter, anterior–posterior and transversal diameters, T1–T12 length, and sternal length. There was no significant difference in thoracic dimensions and volume between scoliosis and reference groups in either girls or boys. Thoracic volume correlated with weight and with sitting height. The transversal diameter represented ∼30%, the anterior–posterior diameter 20%, and the thoracic perimeter 100% of sitting height. Mild and moderate scoliosis does not affect thoracic diameters and volume at any stage of growth. Relationships between thoracic parameters and sitting height are valuable indicators in clinical practice. They do not differ between normal individuals and scoliotic patients with moderate trunk asymmetry.